Two new dinoflagellate cyst species and their biostratigraphical application in the Eocene and Oligocene of the North Sea. (3rd April 2021) - Casas-Gallego, Manuel; Gogin, Iakov; Vieira, Manuel
Abstract: The Cenozoic of the North Sea is among the best-documented stratigraphical successions in the world, and multiple palynological events have been recognised for chronostratigraphical control across the region. The ever-increasing number of wells studied for hydrocarbon exploration and production results in the generation of new biostratigraphical data that constantly increase our palynological knowledge of the area. Here we describe two new dinoflagellate cyst species from an Lower Eocene (Ypresian) to Lower Oligocene (Rupelian) succession in Gannet Field (UK Central North Sea). These are Reticulatosphaera valdereticulata sp. nov., a short-lived Rupelian index taxon, and Alisocysta heilmannii sp. nov., previously informally known as Alisocysta sp. 2, which is an Ypresian marker widely used by biostratigraphers working the North Sea region. The development of a dense network of trabeculae connecting the processes distally allows Reticulatosphaera valdereticulata sp. nov. to be clearly distinguished from the closely similar Reticulatosphaera actinocoronata . The main diagnostic feature in Alisocysta heilmannii sp. nov. is the development of delicate penitabular septa. Both species show widespread palaeogeographical distribution across the North Sea region. We also document the diverse palynofloras in which the two new species are encountered and discuss biostratigraphical application and palaeoenvironmental settings.